2016
DOI: 10.4322/rca.2440
|View full text |Cite
|
Sign up to set email alerts
|

Teores de flavonoides e nutrientes em plantas de noni cultivadas em solos com atributos químicos contrastantes

Abstract: Adubação Metabolismo secundário Relação solo-planta KEYWORDS Fertilization Secondary metabolism Relation soil-plant RESUMO: O noni (Morinda citrifolia) tem sido utilizado como planta medicinal em diversos países do mundo, inclusive no Brasil e principalmente na região amazônica, por conter substâncias com ação antioxidantes, principalmente os flavonoides. No entanto, não existem estudos conclusivos sobre a composição nutricional, bem como se o teor de flavonoides varia entre as partes da planta e se são influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The increase of leaf manganese is in accordance with the report of Ranade-Malvi (2011), who reported a synergistic effect between K and Mn, in which the nutrient's increase contributed to a greater absorption of K. Our results are also in accordance with Amorim et al (2015), who observed a linear increase in foliar Mn content in guava plants that received potassic fertilization from 0.0 to 2.2 kg plant -1 for three consecutive cycles. Despite the increase of Mn content with the application of organomineral fertilization, these values are below the ranges of 1.576 to 2.329 mg kg -1 (Silva et al, 2014a) and 1.075 to 1.888 mg kg -1 (Teixeira et al, 2016) obtained in the same culture and below the range of 80 to 100 mg kg -1 , which is considered sufficient for coffee cultivation (Malavolta et al, 1997). Similar results to those reported in Figure 4B were presented by Anjos et al (2015) who observed that by applying KCl in the soil, the number of fruits per plant was elevated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The increase of leaf manganese is in accordance with the report of Ranade-Malvi (2011), who reported a synergistic effect between K and Mn, in which the nutrient's increase contributed to a greater absorption of K. Our results are also in accordance with Amorim et al (2015), who observed a linear increase in foliar Mn content in guava plants that received potassic fertilization from 0.0 to 2.2 kg plant -1 for three consecutive cycles. Despite the increase of Mn content with the application of organomineral fertilization, these values are below the ranges of 1.576 to 2.329 mg kg -1 (Silva et al, 2014a) and 1.075 to 1.888 mg kg -1 (Teixeira et al, 2016) obtained in the same culture and below the range of 80 to 100 mg kg -1 , which is considered sufficient for coffee cultivation (Malavolta et al, 1997). Similar results to those reported in Figure 4B were presented by Anjos et al (2015) who observed that by applying KCl in the soil, the number of fruits per plant was elevated.…”
Section: Discussionmentioning
confidence: 98%
“…In Brazil, noni was introduced at the beginning of the twenty-first century in São Luís city, located in Maranhão State. Scientific information regarding soil fertility and the nutritional needs of the noni plant is not widely available in the literature in Brazil or worldwide (Teixeira et al, 2016). Due to this lack of information, noni nutritional requirements are estimated using coffee trees (Coffea arabica) as a reference, given that both belong to the same family (Cavalcante et al, 2014;Silva et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%